Nutrition parentérale et sclérose latérale amyotrophique (SLA) - Desport, Jean-Claude; Verschueren, Annie; Juntas-Morales, Raul; Kadaoui El-Abbassi, Marie Christine; Desnuelle, C; Jésus, Pierre; Fayemendy, Philippe; Couratier, Philippe (Nutrition clinique et métabolisme, 2019)
Amyotrophic lateral sclerosis (ALS) is a neuromuscular disease with a severe prognosis, leading to disorders that promote the occurrence of undernutrition. This is an independent factor of survival in this disease. However, the digestive tract is most often functional. For reasons of difficulty in setting up enteral nutrition, or refusal of patients, parenteral nutrition (PN) has been proposed in some cases. The objective of the study was to review literature data regarding PN during ALS.The various articles in the literature were analyzed in the framework of an interprofessional thematic workshop and a detailed review.There were only three articles on this subject, all of French origin, mono or multicentric, and representing 161 patients. Only one article was in part prospective. Patients were selected on the usual indications of PN or the presence of a vital capacity<50%, or the combination of frontotemporal dementia. Infusions were performed using injection sites or peripherally inserted central catheters (PICC lines). The supervision was medico-dietary. These were patients whose evolution had been long, and their life under PN was very short. The prevalence of PN-related infections was in the range of usual values, and that of thromboses was higher. The quality of life of patients was not specified.PN in ALS is possible in late-stage patients. The technique should be reserved for contraindications of enteral nutrition, but a case-by-case discussion is needed. The present study made proposals for practical recommendations.